Dividend behaviour: different market segmentations - Shafai, Nor Anis; Abdul Rahim, Norhuda; Bulot, Norhisam; Md. Nassir, Annuar; Kamarudin, Fakarudin (Faculty of Applied Sciences of WSB University, 2021)
This research explores the dynamics of dividend behaviour of Lintner’s model in three distinct regimes with three different market segmenta-tions, namely Singapore, Malaysia, and Saudi Arabia. In particular, Singapore, Malaysia, and Saudi Arabia each have some interesting features that make this study suitable for policy recommendations to other Asian countries and countries in other parts of the world, espe-cially in the same market segmentation. Therefore, it will be intriguing to see if these three countries adopt stable cash dividend policies, whether they smooth out dividends, and to determine the speed of adjustment of dividends towards a long-run target payout ratio. The study used the top 100 listed firms in each country using the Gener-alised Method of Moments (GMM) for the period of 2007 to 2016. The results clearly demonstrate that Saudi Arabian firms have the smooth-est and most stable dividend payout, followed by Malaysia which has a moderate speed of adjustment suggesting fairly stable dividends arising from a positive change in earnings, while Singapore has a sig-nificantly high speed of adjustment indicating no smoothing. Based on these findings, Saudi Arabian firms practise smoothing and have stable dividends. Although a great deal of research has been done us-ing a partial adjustment model, no evidence has been provided on the three different markets. Most of the research focused on developed markets rather than emerging ones. This could therefore contribute to the different legal and statutory systems that exist in these countries. The difference hinders the overall view of the results obtained from the three markets.